Механізм взаємодії примежового шару полімерних мембран із газовим оточенням - Bulavin, L. A.; Vergun, L. Yu.; Zabashta, Yu. F.; Svechnikova, O. S. (Publishing house "Academperiodika", 2018)
The initial stage at the penetration of air molecules through a polymer membrane has been studied experimentally. A transient process giving rise to an equilibrium between the gas and the boundary layer of the membrane is revealed. This process looks like damped pressure oscillations associated with a periodic shape changes of polymer chains in the boundary layer driven by the “ball–globule” transition. A hypothesis is put forward that a similar phenomenon governs the influence of atmospheric pressure variations on the human organism.